The best planned city in the world : Olmsted, Vaux, and the Buffalo park system - Kowsky, Francis R., 1943- (Designing the American park., 2013)
Beginning in 1868, Frederick Law Olmsted and Calvert Vaux created a series of parks and parkways for Buffalo, New York, that drew national and international attention. The improvements carefully augmented the city’s original plan with urban design features inspired by Second Empire Paris, including the first system of “parkways” to grace an American city. Displaying the plan at the Centennial Exposition in Philadelphia, Olmsted declared Buffalo “the best planned city, as to streets, public places, and grounds, in the United States, if not in the world.” Olmsted and Vaux dissolved their historic partnership in 1872, but Olmsted continued his association with the Queen City of the Lakes, designing additional parks and laying out important sites within the growing metropolis. When Niagara Falls was threatened by industrial development, he led a campaign to protect the site and in 1885 succeeded in persuading New York to create the Niagara Reservation, the present Niagara Falls State Park. Two years later, Olmsted and Vaux teamed up again, this time to create a plan for the area around the Falls, a project the two grand masters regarded as “the most difficult problem in landscape architecture to do justice to.” In this book, the author illuminates this remarkable constellation of projects. Utilizing original plans, drawings, photographs, and copious numbers of reports and letters, he brings new perspective to this vast undertaking, analyzing it as a cohesive expression of the visionary landscape and planning principles that Olmsted and Vaux pioneered.